INFLUENCE OF THIDIAZURON AND INOCULATION WITH Azospirillum brasilense IN THE GROWTH AND PRODUCTIVITY OF HIGHLAND RICE - Garé, L. M.; Buzo, F. S.; Arf, O.; Portugal, J. R.; Silveira, T. L. S.; Meirelles, F. C. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Inoculation with bacteria of Azospirillum genus may contribute with the nitrogen (N) supply and the plant growth, since these microorganisms are also growth promoters. On the other hand the application in the appropriate doses and times of the plant regulator of cytokinin effect thidiazuron (TDZ) may benefit grain yield. Thus, the goal of this work was to evaluate the TDZ dose effect on rice yield, in the presence and absence of leaf inoculation with Azospirillum brasilense. The cultivar ANa 5015 was used in the experimental design of randomized blocks in a 4 x 2 factorial scheme, four TDZ (0,0; 0,5; 1,0 and 1,5g ha-1) doses applied on the occasion of tillering , 30 DAE, and the application of Azospirillum brasilense (presence or absence) at a fixed dose at 20 DAE. It was verified that the cultivar ANa 5015 was not responsive to the leaf inoculation with Azospirillum brasilense at the dose of 200 mL ha-1. For TDZ doses applied via leaf, there was a significant variation in plant height, whose dose of 0.41 g ha-1 resulted in a maximum height of 1.11 m. There was no TDZ rate effect on yield, mass of 100 grains, number of panicles per m², grain per panicle and hectolitric mass.